Hubungan Disiplin Kerja Dan Motivasi Kerja Terhadap Semangat Kerja Karyawan KopKar Sampoerna Surabaya - Reygita Arintya Ayu Pramesti; Mei Retno Adiwaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to understand and evaluate how work motivation and work discipline influence the work ethic of KopKar Sampoerna Surabaya employees. This research is included in the type of associative quantitative research. Using a saturated sampling procedure, 50 employees served as the sample size for this study. This research includes interviews and questionnaires to collect data. SmartPLS version 4 is the analysis tool used. The research findings are as follows: 1) work motivation has a positive but not significant effect on the work spirit of KopKar Sampoerna Surabaya employees; and 2) work discipline has a positive but not significant effect on the work spirit of KopKar Sampoerna Surabaya employees Keywords: Work Morale; Work Discipline; Work motivation